2013
DOI: 10.4103/2249-4863.109944
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of paperless partogram as a bedside tool in the management of labor

Abstract: Introduction:The partogram has been heralded as one of the most important advances in modern obstetric care. However, some healthcare practitioners, especially in high-income countries, have questioned its effectiveness. The purpose of this study is to evaluate prospectively the use of a paperless partogram as a bedside tool in the management of labor.Materials and Methods:Women were invited to participate in the trial if they were at 36 to 42 weeks of gestation, and carrying a singleton pregnancy, with a ceph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
4
12
0
Order By: Relevance
“…This finding is in accordance with the recommendation of WHO plotting the action parallel 4 hours after the alert line [3] [4]. Such a timing of intervention was also put forth by Lavender et al [6] and Agarwal et al [12] who reported an average of 4.3 h (4.7 h for primiparous and 3.7 h for multiparous). In the present study we registered 32 cesarean sections (9%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is in accordance with the recommendation of WHO plotting the action parallel 4 hours after the alert line [3] [4]. Such a timing of intervention was also put forth by Lavender et al [6] and Agarwal et al [12] who reported an average of 4.3 h (4.7 h for primiparous and 3.7 h for multiparous). In the present study we registered 32 cesarean sections (9%).…”
Section: Discussionsupporting
confidence: 89%
“…Agarwal et al [12] in India recruited 91 women, of which 13% of induced labor. In an experimental model, they monitored parturients on the basis of Alert estimated time of delivery (ETD) and Action ETD.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Agarwal k et al in Uttar Pradesh observed a rate of 1% caesarean sections with the Paperless partograph. 8 Another study conducted by Fatouh E et al in Egypt from 1st March to last of August 2014 observed a CS rate of 23.1% with the Paperless partograph. 9 Thus the paperless partograph was found similar and effective in monitoring labour as compared to the WHO partograph.…”
Section: Discussionmentioning
confidence: 94%
“…Study from India, Agarwal et al included 91 women, of which 13% was induced labor. 16 They monitored women in labour on the basis of Alert estimated time of delivery (ETD) and Action ETD. At the time of the Action ETD, if delivery had not yet occurred, a diagnosis of prolonged labour was made and arrangements were made for emergency caesarean section.…”
Section: Discussionmentioning
confidence: 99%